Pemasaran Puisi Tradisional Artis Roslan Madun - Nur Syafiqah, Binti Roslan. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study is about the Marketing of Traditional Poetry Artist Roslan Madun as an artistic folk song Poet and Folk Song of Pahang, This study focuses 011 how marketing methods conducted by Roslan Madun in maintaining his title as a Traditional Artist, The objective of this study is how the traditional poems of Roslan Madun artist are promoted and the extent marketing of Roslan Madun's album through Marketing Mix, This study applies a qualitative methodology using interviews as a research instrument, The findings show that Roslan Madun's used the Traditional Poetry marketing and Marketing album through Marketing Mix to retain his title as a Traditional Artist.